Swimming Energy Economy in Bottlenose Dolphins Under Variable Drag Loading - van der Hoop, Julie M.; Fahlman, Andreas; Shorter, K. Alex; Gabaldon, Joaquin; Rocho-Levine, Julie; Petrov, Victor; Moore, Michael J. (Frontiers in Marine Science, 2018)
Instrumenting animals with tags contributes additional resistive forces (weight, buoyancy, lift, and drag) that may result in increased energetic costs; however, additional metabolic expense can be moderated by adjusting behavior to maintain power output. We sought to increase hydrodynamic drag for near-surface swimming bottlenose dolphins, to investigate the metabolic effect of instrumentation. In this experiment, we investigate whether (1) metabolic rate increases systematically with hydrodynamic drag loading from tags of different sizes or (2) whether tagged individuals modulate speed, swimming distance, and/or fluking motions under increased drag loading. We detected no significant difference in oxygen consumption rates when four male dolphins performed a repeated swimming task, but measured swimming speeds that were 34% (>1 m s-1) slower in the highest drag condition. To further investigate this observed response, we incrementally decreased and then increased drag in six loading conditions. When drag was reduced, dolphins increased swimming speed (+1.4 m s-1; +45%) and fluking frequency (+0.28 Hz; +16%). As drag was increased, swimming speed (-0.96 m s-1; -23%) and fluking frequency (-14 Hz; 7%) decreased again. Results from computational fluid dynamics simulations indicate that the experimentally observed changes in swimming speed would have maintained the level of external drag forces experienced by the animals. Together, these results indicate that dolphins may adjust swimming speed to modulate the drag force opposing their motion during swimming, adapting their behavior to maintain a level of energy economy during locomotion. Summary Statement: Biologging and tracking tags add drag to study subjects. When wearing tags of different sizes, dolphins changed their swimming paths, speed, and movements to modulate power output and energy consumption.